Fire blight rootstock infections causing apple tree death: A case study in high-density apple orchards with Erwinia amylovora strain characterization - Aćimović, Srđan G.; Santander, Ricardo Delgado; Meredith, Christopher L.; Pavlović, Žaklina M. (Frontiers in Horticulture, 2023)
A devastating outcome of fire blight in apple trees is the infection of rootstock, which leads to canker development. Fire blight cankers are infected zones of bark on perennial branches, trunk, or rootstock that develop after fire blight pathogen Erwinia amylovora invades wood. Cankers can girdle the trunk, branches and rootstock leading to tree death and production losses, especially significant in high-density orchards. An accurate diagnosis of trunk and rootstock blight is a top challenge for apple growers because fire blight cankers can be visually misdiagnosed with cankers caused by less frequent Oomycete and fungal pathogens (e.g., Phytophthora spp., Botryosphaeria dothidea, B. obtusa, Valsa mali). In addition, detecting E. amylovora in apple rootstocks is essential because this pathogen also causes asymptomatic infections. Accurate fire blight diagnosis is necessary to inform the complete removal of infected trees from the orchard and help replant the orchard while preventing further pathogen dissemination. To determine apple tree losses caused by fire blight rootstock infections, PCR was used to detect E. amylovora in symptomatic and asymptomatic rootstocks for two years. Rootstock canker incidence and tree death were rated in selected infection foci on seven commercial apple orchards in New York. Each infection focus consisted of central rootstock-blighted tree and the nearest surrounding edge trees showing no rootstock blight. E. amylovora strains collected from these seven orchards and other orchards in New York were characterized. In the first year most of the orchards showed E. amylovora detection rates of 10.7 – 45.3% in asymptomatic rootstocks on edge trees immediately surrounding visibly infected i.e. rootstock-blighted trees central trees. One year later, 20.8 – 56.3% cankered rootstocks were detected on the edge trees and from zero to 35.4% dead edge trees were recorded. However, the PCR from sampled edge rootstocks one year later showed no pathogen detections. E. amylovora rootstock strains showed slight variability in enzymatic activity, copper sensitivity, virulence, and exopolysaccharide production. These results elucidate the role and importance of rootstock infections for apple tree survival, the presence of latent fire blight infections, and the valuable utility of molecular detection to assist apple tree removal after epidemics.